Agency relationships of project-based firms. Issue 7 (October 2021) - Ahola, Tuomas; Ståhle, Matias; Martinsuo, Miia
Highlights: Project-based firms rely on various agents, such as subcontractors and consultants, to carry out activities on their behalf We describe characteristics of agency relationships during front-end, implementation, and operations phases of the project life cycle. We found agency relationships to vary according to actor goals, information asymmetries, and actor risks. We propose a typology of agency relationships consisting of: operational, trustful, volatile, and strategic relationships. Abstract: Throughout the project life cycle, project-based firms (PBFs) rely on various agents, such as subcontractors and consultants, to carry out activities on their behalf. Although a considerable body of literature has discussed when and how PBFs use agents, little is known about the nature of the agency relationships between PBFs acting as principals and their agents and how these relationships may be associated with the practices used by PBFs to govern their agents' behaviour. The purpose of this conceptual study is to provide further insight into the characteristics of PBFs' agency relationships and to identify and describe alternative approaches used for managing them. Our analysis reveals that PBFs' agency relationships differ significantly regarding actor goals, risks, and availability of information across the project life cycle. Based on our findings, we propose a typology of the upstream agency relationships of a PBF consisting of four ideal types: operational, trustful, volatile, and strategic agency relationships. We argue that the development of agency relationships is a dynamic process which is contingent to the temporal orientation of the principal and the agent as well as congruence of goals between the principal and the agent.